The Tokyo Air Raids in the Words of Those Who Survived, 被災者が語る東京空襲 - Bret Fisk (Japan Focus)
This article provides introduces the types of first-person accounts of the civilian experience of the Tokyo air raids. Examples of such accounts are given under the headings: "Complete Personal Narratives," "Incomplete Episodes and Incidents," and "Sites of Mass Suffering."